Inductive effect of MXene membrane influenced by β‐cyclodextrin intercalation. (11th September 2022) - Yang, Haodong; Chen, Huan; Chen, Zhe; Li, Yong; Yao, Lei; Wang, Geming; Deng, Quanrong; Fu, Ping
Abstract: Two‐dimensional nanomaterials could be potentially applied in the field of brain–computer interface due to their significant inductive effect during ion permeation. In order to tune the inductive signal through the microstructure, a membrane based on MXene‐grafted β‐cyclodextrin (β‐CD) was prepared, and its electrochemical performance was recorded. The experimental results confirmed that β‐CD has been successfully intercalated into the gallery between the MXene sheets, and the intercalation induced a weaker inductive effect of MXene in the ion diffusion process. Moreover, the results indicated that easier ion diffusion through the membrane could result in weaker inductance. Besides, the experimental results were roughly analyzed by the back‐propagation (BP) neural network to compare the contribution of the influence factors. The results suggested that tunable inductance can be achieved by constructing a certain interlay spacing of MXene, which could be potentially used to design microsized inductors in biological applications.